Comparison of Athletes’ Proneness to Depressive Symptoms in Individual and Team Sports: Research on Psychological Mediators in Junior Elite Athletes - Nixdorf, Insa; Frank, Raphael; Beckmann, Jürgen (Frontiers in Psychology, 2016)
Depression among elite athletes is a topic of increasing interest and public awareness. Currently, empirical data on elite athletes’ depressive symptoms are rare. Recent results indicate sport related mechanisms and effects on depression prevalence in elite athlete samples; specific factors associated with depression include overtraining, injury and failure in competition. One such effect is that athletes competing in individual sports were found to be more prone to depressive symptoms than athletes competing in team sports. The present study examined this effect by testing three possible, psychological mediators based on theoretical and empirical assumptions: namely, cohesion in team or training groups; perception of perfectionistic expectations from others; and negative attribution after failure. In a cross-sectional study, 199 German junior elite athletes (Mage = 14.96; SD = 1.56) participated and completed questionnaires on perfectionism, cohesion, attribution after failure, and depressive symptoms. Mediation analysis using path analysis with bootstrapping was used for data analysis. As expected, athletes in individual sports showed higher scores in depression than athletes in team sports (t(197) = 2.05; p < .05; d = .30). Furthermore, negative attribution after failure was associated with individual sports (β = .27; p < .001), as well as with the dependent variable depression (β = .26; p < .01). Mediation hypothesis was supported by a significant indirect effect (β = .07; p < .05). Negative attribution after failure mediated the relationship between individual sports and depression scores. Neither cohesion nor perfectionism met essential criteria to serve as mediators: Cohesion was not elevated in either team or individual sports, and perfectionism was positively related to team sports. The results support the assumption of previous findings on sport specific mechanisms (here the effect between individual and team sports) contributing to depressive symptoms among elite athletes. Additionally, attribution after failure seems to play an important role in this regard and could be considered in further research and practitioners in the field of sport psychology.